Efikasi Akademik dan Prokrastinasi Akademik Sebagai Prediktor Prestasi Akademik - Dami, Zummy Anselmus; Loppies, Paula Alfa (Kelola: Jurnal Manajemen Pendidikan, 2018)
The purpose of this research is to investigate the relationship between significance or know the academic efficacy and procrastination academic with achievement students academic of project study guidance and counseling, Teaching and Education Faculty University PGRI East Nusa Tenggara. The number of samples used in the study as much as 92 students drawn from population 1180 includes force 2009 as much as much as 102 students 2010 force 205 students, 2011 as much as 368 students, and force as many as 505 2012 student. The sampling technique used is the purposive sampling technique. Tool collecting data using a detailed questionnaire with Likert scale, which consists of a detailed questionnaire for academic procrastination and academic efficacy. While the achievement of student learning is measured based on the CPI. The analysis used in this study is the technique of correlation of Product Moment with the help of SPSS Version 18.0. The first hypothesis test results showed that the relationship between academic procrastination and academic achievement, known (r) correlation coefficient between academic procrastination and academic achievement of 0.015 with p 0.890 > 0.05 negative correlation, direction and with the guidelines of the wear level of significance of 5%, obtained p 0.890 > 0.0.5 then correlation between academic procrastination and academic achievement is declared not significant. The second hypothesis test results showed a relationship between academic efficacy with academic achievement, known coefficient of correlation (r) between academic efficacy and academic achievement -0.004 0.970 > with p 0.05, direction correlation negative and wear guidelines significance level 5%, obtained p 0.970 > 0.05 then correlation between academic efficacy with academic achievement is expressed is not significant. While the third hypothesis test results showed the absence of significant correlation between academic procrastination and academic efficacy simultaneously toward academic achievement with the retrieved R square (coefficient of determination) of 0000, and the coefficient correlation of 0.015 with 0.990 > p 0.05. Further, it is known from the Fcount of 0.010 of Ftable of 3.10, so that H0 is accepted and Ha was rejected.